Endoscopic submucosal dissection using a thulium laser: preliminary results of a new method for treatment of gastric epithelial neoplasia - Cho, Jun-Hyung; Cho, Joo Young; Kim, Mi-Young; Jeon, Seong Ran; Lee, Tae Hee; Kim, Hyun Gun; Jin, So Young; Hong, Su Jin (Endoscopy, 2013)
Background and study aim: This study aimed to evaluate the feasibility of a novel laser system for endoscopic submucosal dissection (ESD) of gastric epithelial neoplasia. Patients and methods: A total of 10 patients underwent ESD by a single expert endoscopist. A thulium 2-μm wavelength laser system was used for ESD procedures. Instead of using endoscopy knives, a 550-μm flexible silica fiber was inserted through the working channel of the endoscope. Results: In all patients, ESD was completed using only the thulium laser, without the need for endoscopy knives. The median total procedure time was 49 minutes (range 35 – 203). In 8 /10 patients (80 %), no active bleeding was observed during ESD. The final pathologic mapping revealed low-grade dysplasia (n = 4), differentiated adenocarcinoma (n = 5), and signet ring cell carcinoma (n = 1). Curative resection was achieved in 9 /10 patients (90 %). There were no significant complications, such as delayed bleeding or perforation. Conclusions: The thulium laser system was feasible in ESD of gastric epithelial neoplasia.